High-resolution HPLC-ESI-MS characterization of the contact sites of the actin-thymosin ?(4) complex by chemical and enzymatic cross-linking - Knop, Jana; App, Christine; Horn, Anselm; Iavarone, Federica; Castagnola, Massimo; Hannappel, Ewald (Biochemistry, 2013)
Thymosin ?4 sequesters actin by formation of a 1:1 complex. This transient binding in the complex was stabilized by formation of covalent bonds using the cross-linking agents 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and a microbial transglutaminase. The localization of cross-linking sites was determined after separating the products using SDS-PAGE by tryptic in-gel digestion and high-resolution HPLC-ESI-MS. Three cross-linked fragments were identified after chemical cross-linking, indicating three contact sites. Because the cross-linked fragments were detected simultaneously with the corresponding non-cross-linked fragments, the three contact sites were not formed in parallel. K3 of thymosin ?4 was cross-linked to E167 of actin, K18 or K19 of thymosin ?4 to one of the first three amino acids of actin (DDE), and S43 of thymosin ?4 to H40 of actin. The imidazole ring of histidine was proven to be an acyl acceptor for carbodiimide-mediated cross-linking. Molecular modeling proved an extended conformation of thymosin ?4 along the subdomains 1 to 3 of actin. The enzymatic cross-linking using a microbial transglutaminase led to the formation of three cross-linking sites. Q41 of actin was cross-linked to K19 of thymosin ?4, and K61 of actin to Q39 of thymosin ?4. The third cross-linking site was identified between Q41 of actin and Q39 of thymosin ?4, which are simultaneously cross-linked to K16, K18, or K19 of thymosin ?4. When both cross-linking reactions are taken together, the complex formation of actin by thymosin ?4 is more likely to be flexible than rigid and is localized along the subdomains 1 to 3 of actin.
EVALuna2:4937